2018
DOI: 10.1111/1756-185x.13421
|View full text |Cite
|
Sign up to set email alerts
|

Polyarticular evolution and late‐onset psoriasis may be associated with cardiovascular disease in psoriatic arthritis

Abstract: Background and aims:Patients with psoriatic arthritis (PsA) have high prevalence of cardiovascular risk factors (CVRF), and they also show higher rates of cardiovascular disease (CVD). We aimed to corroborate these findings and identify factors associated with these events in our clinical setting. Methods:This cross-sectional study included 340 consecutive patients seen in a tertiary care hospital. The prevalence of CVRF was compared to that of 600 outpatients without inflammatory conditions. To analyze CVD-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
2
2
0
2
Order By: Relevance
“…In another assessment of 2896 patients with PsA, AS or RA, obesity was more prevalent among those with PsA (23.0%) than in those with AS (17.0%) or RA (15.2%) ( 30 ). Similar results have been reported in two retrospective cross-sectional studies by Queiro and colleagues ( 31 , 32 ). One study showed that PsA patients had a significantly higher prevalence of obesity (35.0% vs 22.0%; p<0.0001), hypertension (36.0% vs 23.0%; p<0.0001) and diabetes (13.8% vs 5.0%; p<0.0001) compared with patients without inflammatory conditions ( 32 ).…”
Section: Cardiometabolic Profile Of Spondyloarthritis Patientssupporting
confidence: 92%
“…In another assessment of 2896 patients with PsA, AS or RA, obesity was more prevalent among those with PsA (23.0%) than in those with AS (17.0%) or RA (15.2%) ( 30 ). Similar results have been reported in two retrospective cross-sectional studies by Queiro and colleagues ( 31 , 32 ). One study showed that PsA patients had a significantly higher prevalence of obesity (35.0% vs 22.0%; p<0.0001), hypertension (36.0% vs 23.0%; p<0.0001) and diabetes (13.8% vs 5.0%; p<0.0001) compared with patients without inflammatory conditions ( 32 ).…”
Section: Cardiometabolic Profile Of Spondyloarthritis Patientssupporting
confidence: 92%
“…A obesidade foi mais comum entre os pacientes com AP ou psoríase do que entre os pacientes sem apresentação inflamatória. Além do mais, a obesidade foi mais frequente entre os pacientes com psoríase sem artrite (QUEIRO et al, 2019). No entanto, Eder et al (2017) mostrou resultados diferentes ao observar que a obesidade estava mais associada a AP do que na psoríase sem artrite.…”
Section: Resultsunclassified
“…No entanto, Eder et al (2017) mostrou resultados diferentes ao observar que a obesidade estava mais associada a AP do que na psoríase sem artrite. Além da obesidade, os pacientes com AP apresentam outras comorbidades com frequência mais elevadas como hipertensão, diabetes e tabagismo (QUEIRO et al, 2019;KAINE et al, 2019).…”
Section: Resultsunclassified
“…Obesity is another common cardiovascular risk factor in psoriatic disease [113][114][115]. Obesity is a negative predictor of therapeutic response in PsA [116,117], and on the other hand, evidence shows that weight loss improves disease activity [118].…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 99%